Integrated Mass Transportation Planning for the Development of Medan City Area - Edwart Haloho; Abdi Sugiarto (Journal of Information Technology, computer science and Electrical Engineering, 2024)
This study aims to examine the Integrated Mass Transportation Planning for the Development of Medan City Area. The type of research used in this study is a type of descriptive research with a qualitative approach. To analyze the Integrated Mass Transportation Planning for the Development of Medan City Area, various research methods were used. First, a literature study was carried out that involved a review of official documents related to transportation policies in Medan City, including local regulations, official government reports, and related publications. The data obtained from literature studies, observations, and interviews were then analyzed qualitatively. The results of this analysis are expected to provide a comprehensive picture of the success of the policy in improving Integrated Mass Transportation. The results of the Integrated Mass Transportation Policy research in Medan City can be considered a significant step in efforts to improve public transportation services in the city. By providing coordinated transportation system integration, improved accessibility, and a focus on energy efficiency and passenger safety, Integrated Mass Transportation provides concrete solutions to address various challenges in the provision of public transportation services. Overall, Integrated Mass Transportation is a progressive step that shows the commitment of the City of Medan to improving the quality of life of its residents through the provision of better and sustainable public transportation services. With collaboration between the government, transportation operators, and the community, Integrated Mass Transportation has the potential to be an example for other cities in an effort to improve the quality of public transportation services as a whole.